A thermoelectric generator comprising selenium-doped bismuth telluride on flexible carbon cloth with n-type thermoelectric properties. Issue 8 (15th April 2022) - Kim, Minsu; Park, Dabin; Kim, Jooheon
Abstract: Carbon cloth was used as a flexible substrate for bismuth telluride (Bi2 Te3 ) particles to provide flexibility and improve the overall thermoelectric performance. Bi2 Te3 on carbon cloth (Bi2 Te3 /CC) was synthesized via a hydrothermal reaction with various reaction times. After over 12 h, the Bi2 Te3 particles showed a clear hexagonal shape and were evenly adhered to the carbon cloth. Selenium (Se) atoms were doped into the Bi2 Te3 structure to improve its thermoelectric performance. The electrical conductivity increased with increasing Se-dopant content until 40% Se was added. Moreover, the maximum power factor was 1300 μW/mK 2 at 473 K for the 30% Se-doped sample. The carbon cloth substrate maintained its electrical resistivity and flexibility after 2000 bending cycles. A flexible thermoelectric generator (TEG) fabricated using the five pairs of 30% Se-doped sample showed an open-circuit voltage of 17.4 mV and maximum power output of 850 nW at temperature difference ΔT = 30 K. This work offers a promising approach for providing flexibility and improving the thermoelectric performance of inorganic thermoelectric materials for wearable device applications using flexible carbon cloth substrate for low temperature range application.